Photoluminescence characterization and heat treatment effect on luminescence behavior of BaTa2O6:Dy3+ phosphor - EKMEKÇİ, METE KAAN (WILEY, 2017)
Undoped and Dy3+-doped barium tantalate phosphors were synthesized by the solid-state reaction method at 1425 degrees C. Also, 10mol% Dy3+-doped BaTa2O6 was sintered between 1150 and 1425 degrees C in order to determine temperature effect on structural and luminescence properties. Afterwards, they were characterized by XRD, SEM-EDS and photoluminescence (PL) analyses. PL spectra exhibited the excitation peaks between 300 and 440nm. Two typical emissions were observed at 486.2nm (blue) and 577.7nm (yellow) due to the (F9/2H15/2)-F-4-H-6 and (F9/2H13/2)-F-4-H-6 transitions, respectively. Emission intensities increased with increasing doping concentration of Dy3+ up to 10mol% and then decreased due to the concentration quenching effect. Moreover, depending on the increase in heat treatment temperature, the intensity of emission reached maximum at 1425 degrees C. The calculated CIE chromaticity coordinates of phosphors located in the white light region.
Keywords: luminescence; scanning electron microscopy; tantalum; tantalum compounds; X-ray methods; SPECTROSCOPIC PROPERTIES; ENERGY-TRANSFER; IONS; NANOCRYSTALS; TEMPERATURE; COLOR